Closing knowledge gaps in foreign markets - Petersen, Bent; Pedersen, Torben; Lyles, Marjorie A (Journal of International Business Studies, 2008)
Knowledge and learning are ascribed pivotal roles in firms' internationalization processes: perceived market uncertainties, namely knowledge gaps related to business environments in foreign markets, may curb firms' inclinations to commit resources to these markets. This study explores whether knowledge gaps tend to increase or decrease with time when operating in the foreign market, and it discusses which learning components narrow – or widen – the perceived knowledge gap. A theoretical model is developed based on the internationalization process view and the more recent organizational learning perspective, including such concepts as overconfidence and absorptive capacity. The theoretical model is tested on a set of primary data covering Danish and Swedish firms and their foreign market operations. The results suggest a more subtle relationship between experience and perceived knowledge gaps than the “mechanical” relationship portrayed by the internationalization process view – a relationship in which absorptive capacity and, in particular, overconfidence play important roles.